Multiobjective axiomatic and robust design approaches to mechanical spring design - Feyzioğlu, Ahmet (My University, 2005)
MEKANİK YAY ÜZERİNE ÇOK AMAÇLI AKSİYOMATİK VE ROBUST TASARIM YAKLAŞIMI UYGULAMASI Bu tez çok amaçlı Aksiyomatik ve Robust tasarım yaklaşımı hakkında bilgi verir. Aksiyomatik ve Robust tasarım yaklaşımı kararlaştırılmış amaçlar ile tamamlayıcı bir yol içinde formüle edilmiştir. Bu çalışmamızda temel hedefimiz, tasarım aşamasında sağlamlığın ve dayanıklılığın bütünleştirilmesiyle yayın ağırlığının ve iç mukavemetinin en aza indirilmesidir. Mekanik yay problemi, aksiyomatik tasarımın bağımsızlık aksiyomunu, diklik ve paralellik şartı kavramları ile incelenmekte, tasarım matrisi ile bağımlı ve bağımsızlaştırılabilen tasarım durumları gösterilmektedir. Böylece bazı bölgelerde tasarımın bağımsızlaştırılabileceği gösterilmiş ve sistemin sağlamlığı ve dayanıklılığı arttırılmıştır. Kasım, 2005 Ahmet FEYZİOĞLU IMPLEMENTING MULTIOBJECTIVE AXOMATIC AND ROBUST DESIGN APPROACH ON MECHANICAL SPRING This thesis gives general information about multiobjective axiomatic and robust design approach. An Axiomatic Design approach and a Robust Design approach are formulated in a complementary way with the newly determined multiobjectives. The main target in this study is to minimize mass and shear stress of the spring with integration of robustness and durability at design stage. A mechanical spring problem is examined using independence axiom of the axiomatic design methodology. Semangularity and reangularity concepts are derived and design matrixes are formed to indicate coupled and decoupled cases. Thus, it shows that, there are some regions where it is possible to obtain decoupled design. Then solutions are developed to satisfy systems robustness and durability. November, 2005 Ahmet FEYZİOĞLU
Keywords: Aksiyomatik Tasarım; Makine Mühendisliği; Robust Tasarım